2021
DOI: 10.3390/molecules26041042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Four Extraction Methods of Antioxidant Compounds from Decatropis bicolor in Aqueous Medium Applying Response Surface Design

Abstract: The objective of this paper is to compare conventional, ultrasound, microwave, and French press methods for the extraction of antioxidant compounds from Decatropis bicolor in an aqueous medium. This plant is widely used in Mexican traditional medicine for breast cancer treatment. Despite that, there are few studies on D. bicolor. Two response surface designs were applied to establish the best conditions of the liberation of antioxidants from D. bicolor, which were determined by DPPH• and Ferric Reducing Antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(88 reference statements)
0
6
0
1
Order By: Relevance
“…The size of the steepness and contour ellipticity values exhibited on the response surface can effectively judge the degree of interaction between factors. The steeper the surface, the larger the contour ellipticity (Jaimez-Ordaz et al, 2021;Lin et al, 2020), which represents the strength of the interaction effect. Figure 4 shows that the strength of the interaction effects of BC on hypoglycemic performance was stronger than that of AC and then stronger than that of AB.…”
Section: Response Surface Analysismentioning
confidence: 99%
“…The size of the steepness and contour ellipticity values exhibited on the response surface can effectively judge the degree of interaction between factors. The steeper the surface, the larger the contour ellipticity (Jaimez-Ordaz et al, 2021;Lin et al, 2020), which represents the strength of the interaction effect. Figure 4 shows that the strength of the interaction effects of BC on hypoglycemic performance was stronger than that of AC and then stronger than that of AB.…”
Section: Response Surface Analysismentioning
confidence: 99%
“…For instance, a recent study demonstrated that USAE treatment improved the extraction of both lipophilic and hydrophilic substances from turmeric, ginger and garlic, including vitamin C, total phenols, flavonoids, non-flavonoids and β-carotene [ 43 ]. Similarly, USAE has been successfully used for the extraction of antioxidant compounds from Decatropis bicolor— a medicinal plant from Central America [ 44 ]. In this study, the authors optimized the extraction conditions, such as extraction time, temperature, and sample size [ 44 ].…”
Section: Isolation Of Bioactive Agents From Botanical Sourcesmentioning
confidence: 99%
“…Similarly, USAE has been successfully used for the extraction of antioxidant compounds from Decatropis bicolor— a medicinal plant from Central America [ 44 ]. In this study, the authors optimized the extraction conditions, such as extraction time, temperature, and sample size [ 44 ].…”
Section: Isolation Of Bioactive Agents From Botanical Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Las propiedades físicas determinadas fueron: eje mayor, eje menor, espesor, peso, volumen y color. La composición proximal se realizó de acuerdo a la metodología de la AOAC, mientras que el contenido de minerales se determinó de acuerdo a la metodología establecida por la EPA, (Jaimez-Ordaz, J., et al, 2021).…”
Section: Apreciables Lectores De Pädiunclassified